What if Video See-Through in HMDs Changes How Accurately We Perform Tasks? - Domingues, Gustavo Camargo; Vieira, Vitor; Yoshida, Leina; de Oliveira, Leticia; Peres, Fabiana; Mauricio, Claudio; Nunes, Fatima; Teixeira, João Marcelo; Neto, Amadeo (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
This paper explores the impact of video see-through head-mounted display devices on user perception and accuracy during activity execution. As augmented reality technologies evolve from cumbersome systems to advanced, self-contained units like HMDs, they offer enhanced freedom and immersive interactions with digitally augmented environments. Despite significant strides in this field, there is a comparative scarcity of research evaluating the practical effectiveness of these technologies in real-world applications. This study focuses on VST systems, which have gained substantial commercial traction over optical see-through systems due to their cost-effectiveness and ease of integration. This research assesses the precision and accuracy of these devices through a two-stage experiment involving dart throwing and bottle handling tasks to determine their applicability in both precise and everyday activities. Using a Meta Quest 3 as the target HMD, the experiment evaluates performance with and without the device, aiming to identify any significant differences in task execution. This paper aims to fill the gap in literature by providing empirical evidence on the feasibility of VST HMDs in enhancing user interaction within a mixed reality context, thereby contributing to the broader application and democratization of VST technology.